FRI0150 Is vitamin d deficiency a factor in the association of bronchiectasis and rheumatoid arthritis?. (23rd January 2014) - Chapman, K. E.; Aiken, L.; Rizzo, S.; Hamilton, J.; Kelly, C.
Abstract : Background: It is established that Vitamin D deficiency is common in patients with Rheumatoid Arthritis (RA)[1 ], and that the prevalence of chronic infection is increased in RA [2 ]. Vitamin D deficiency has been proposed as a factor in the increased propensity of RA patients to develop chronic infection. As bronchiectasis is particularly well described in association with RA, this model of chronic infection offers an excellent model to test our hypothesis. Objectives: Our objectives were to test the concept that vitamin D deficiency is a factor in RA patients developing chronic infection. We did this by assessing the potential role of vitamin D deficiency in a cohort of patients with both RA and bronchiectasis. As anti cyclic citrullinated peptide antibodies (ACPA) are elevated in patients with active RA, we were also keen to assess any potential relationship between vitamin D levels and ACPA titres. Methods: We identified all patients with prevalent diagnoses of RA (EULAR criteria 2010) and bronchiectasis (confirmed by high resolution computed tomography) using our centre database. We collected demographic details and measured Vitamin D and ACPA titres for both this group of patients, and for an age and gender matched control group of RA patients with no evidence of lung disease. We calculated the median age, gender ratio, median vitamin D levels and ACPA titres in both groups for comparison. We calculated the number of patients deficient in vitamin D, defined as a level below 30nmol/l. Results: We identified 42 patients with both RA and bronchiectasis, and excluded 8 of these due to incomplete data. In the remaining 34 patients: 21 (62%) were female, giving a female to male ratio of 1.6 with a median (range) age of 70 (55-81) years. The median (range) vitamin D level for the group was 34.6 (9.5 -130) nmol/l and 15 patients (44%) were vitamin D deficient. The median (range) vitamin D level among RA controls was 39.4 (18 – 103) nmol/l and 40% of the controls were vitamin D deficient [NS]. In patients with RA and bronchiectasis, the median (range) titre of ACPA was 185.5 (1.5 - >340) and 6 (17%) had a negative ACPA test. Among the RA controls, the median (range) ACPA titre was 89 (0 – 340) and 40% patients were ACPA negative (P = 0.01). There was no significant correlation between levels of vitamin D and ACPA titres (r = 0.26). Conclusions: Our results showed no significant reduction in vitamin D levels in patients with RA and bronchiectasis, although vitamin D deficiency was common in both groups as expected. There was no correlation between vitamin D levels and ACPA titres. Patients with RA and bronchiectasis had elevated ACPA titres when compared to RA controls and were more likely to be ACPA positive. Hence, although we have not shown vitamin D deficiency to be associated with chronic lung infection, increased ACPA titres suggest that such patients may have more active or severe RA. References: Rossini et al, Vitamin D deficiency in rheumatoid arthritis: prevalence, determinants and associations with disease activity and disability, Arthritis Research and Therapy, 2010, 12:R216 Puntis D, Malik S, Saravanan V, Rynne M, Heycock C, Hamilton J and Kelly CA. Urinary tract infections in patients with rheumatoid arthritis. Clin Rheumatol 2012 DOI 10.1007/s10067-012-2129-7 Disclosure of Interest: None Declared